9 rules for successful crowdsourcing - Libert, Barry (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from We are smarter than me: How to unleash the power of crowds in your business (9780132244794) by Barry Libert and Jon Spector. Discover today's crowdsourcing best practices--and avoid the dangers!"--Resource description page